2016
DOI: 10.1126/sciimmunol.aah4609
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of HDAC8 and HDAC9 by microbial short-chain fatty acids breaks immune tolerance of the epidermis to TLR ligands

Abstract: Epidermal keratinocytes participate in immune defense through their capacity to recognize danger, trigger inflammation, and resist infection. However, normal skin immune function must tolerate contact with an abundant community of commensal microbes without inflammation. We hypothesized that microbial environmental conditions dictate the production of molecules that influence epigenetic events and cause keratinocytes to break innate immune tolerance. , a commensal skin bacterium, produced the short-chain fatty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
121
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(127 citation statements)
references
References 42 publications
(52 reference statements)
2
121
0
Order By: Relevance
“…2). Some of these lipids, such as sapienic acid, can have antimicrobial activities 16 , while others, such as triglycerides, can be metabolized by microbes 17 into free fatty acids and di- and monoglycerides that can be bioactive against other microbes or stimulatory to host cells 18 .…”
mentioning
confidence: 99%
“…2). Some of these lipids, such as sapienic acid, can have antimicrobial activities 16 , while others, such as triglycerides, can be metabolized by microbes 17 into free fatty acids and di- and monoglycerides that can be bioactive against other microbes or stimulatory to host cells 18 .…”
mentioning
confidence: 99%
“…Members of Corynebacterium species promote the expansion of IL-17-producing gd T cells through mycolic acid, a component of the cell envelope (Ridaura et al, 2018). In human skin, C. acnes produce short-chain fatty acids (SCFAs) in anaerobic conditions with a lipid substrate for fermentation, and SCFA-mediated histone deacetylase inhibition modulates inflammatory response of epidermal keratinocytes to TLR ligands (Sanford et al, 2016). Investigating how commensal-derived signals including bacterial elements and their metabolites prime skin immunity, and the precise receptor-ligand interactions involved, require further exploration.…”
Section: Cross-regulation Of Host Immunity and The Microbiota In Healmentioning
confidence: 99%
“…Butyrate regulates gene expression by inhibiting histone deacetylases (HDAC) [36], in particular butyrate inhibits HDAC1 and HDAC3 [37]. Also propionate acts as a less potent HDAC inhibitor [38]. Recently it has been suggested that inhibition of HADAC may increase Tregs development and function, hence this could be one of the mechanism by which GM enhances Treg generation in the gut [39].It has also been suggested that, depending on the cytokines milieu, interaction between SCFA and FFAR influences T cells differentiation not only towards Tregs, but also towards effector T cells.…”
Section: Gm Influences Immune Systemmentioning
confidence: 99%